The Quality of Care Delivered in a Simulation Center: A Benchmark Study. Issue 1 (6th January 2023) - Maguire, Mary Beth R.; White, Anne; Brown, Austin
Abstract : Background: A standardized survey to describe the quality of care received from prelicensure nursing students during simulation can measure simulation program effectiveness. Purpose: The purpose of this study was to compare national Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey data with data received from standardized patients (SPs) using a modified HCAHPS survey. Methods: SPs completed a modified HCAHPS survey immediately following each in-person simulated encounter. One year of SP responses (N = 385) from one baccalaureate nursing program was compared with the national HCAHPS survey data from the same time. Results: All SP responses were less than the national proportions. However, when the level of stringency was adjusted, the responses more similarly aligned to the national proportions. Conclusions: Findings suggest HCAHPS data can be used to model correlates of the quality of care SPs receive during simulation events.